Manejo florestal não madeireiro das famílias extrativistas da reserva extrativista Mapuá, comunidade santíssima trindade, Rio Aramã, Breves (PA) - SILVA, Alberis Gomes da (2021)
This Action Plan was built collectively, based on the demands of the Santissima Trindade Breves Community, Pará state (Amazon region, Brazil) and is effective through the dialogue of knowledge between traditional peoples, communities and academia. The objective is to strengthen the sustainable non-timber management carried out by extractive families in the community, as a path to sustainability and seeks to reflect on the contribution that the Extractive Reserve (RESEX) has to the Forest’s People. The Action Plan was structured from the research of the Communities Times with contributions and discussions raised in the course of the study and participatory research and with the University Time according to what is foreseen in the Pedagogical Political Project undergraduate and bachelor's degree in Ethnodevelopment from the Federal University of Pará (UFPA). In this sense, the dialogues and research had the direct and collective participation of the community and brought the importance and contribution of RESEXs to the conservation and protection of the forest, after 30 years of murder of the creator, unionist and activist Chico Mendes. Non-Timber Forest Products are the main income providers in the Santíssima Trindade Community. For this reason, this Action Plan prioritized dialogue with the community about the obstacles and problems existing in the Extractive Reserves, the “large enterprises” and agribusiness strategies that affect the Resex and Traditional Peoples, as well as working with the resistance tools, the need for autonomy and organization as Traditional Communities. Local community autonomy is fundamental for social processes.